Synergistic Control of Shrinkage and Mechanical Properties in Expansive Soil Slurry via Coupled Cement–Fiber Reinforcement - Dongxing Zhang; Yuchen Wang; Zhaohong Zhang; Zhenping Sun; Chengzhi Wang; Shuang Zou (Buildings, 2025)
This study elucidates the synergistic effects of polypropylene fiber and cement (physical–chemical) on stabilized expansive soil slurry. A comparative analysis was conducted on the fluidity, 28-day mechanical strength, and shrinkage properties (autogenous and drying) of slurries with different modifications. The underlying mechanisms were further investigated through Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) analysis. Results demonstrate that the cement addition substantially enhanced fluidity, mechanical strength, and early-age volume stability through hydration. However, it was insufficient to mitigate long-term drying shrinkage at low dosages. Conversely, incorporating 0.5% polypropylene fiber reduced slurry fluidity but markedly improved flexural strength. Crucially, a pronounced synergistic effect was observed in the co-modified slurry; the specimen with 20% cement and 0.5% fiber exhibited a 28-day drying shrinkage of only 0.57%, a performance comparable to the specimen with 60% cement and no fibers. Microstructural analysis revealed that cement hydration products created a robust fiber-matrix interfacial transition zone, evidenced by C-S-H gel enrichment. This enhanced interface enabled the fibers to effectively bridge microcracks and restrain both autogenous and drying shrinkage. This research validates that the combined cement–fiber approach is a highly effective strategy for improving expansive soil slurry, yielding critical enhancements in flexural performance and long-term dimensional stability while allowing for a significant reduction in cement content.